Temperature Monitoring System Internet of Things-based Electric Cars (IoT) - Ardana, Regina Olivia Fitri; Ma'arif, Alfian; Salah, Wael; Sharkawy, Abdel-Nasser; Marhoon, Hamzah M (Association for Scientific Computing Electrical and Engineering (ASCEE), 2025)
Electric cars are a means of transportation that can meet the mobility needs of the community but are still environmentally friendly because they have no air pollution or exhaust emissions. Electric cars at Ahmad Dahlan University began to be made since 2019. In the effort to develop this electric car, there are several obstacles in monitoring the tools on the electric car during the race. So this research provides an Internet of Things-Based Battery and BLDC Motor Temperature Monitoring System on the ADEV 01 Monalisa Electric Car. which is made using several components including the DS18B20 Sensor, ADEV BLDC Motor, NodeMCU ESP32, LCD (Liquid Crystal Display). This research method develops a temperature monitoring system on an Internet of Things-based electric car using the Thinger.io platform. in this study tested the effectiveness of the DS18B20 temperature sensor in monitoring the temperature of the Battery and BLDC Motor on the ADEV 01 Monalisa electric car. the tests carried out were static testing, dynamic testing, testing data transmission to the Thinger.io platform, and distance testing. The results of testing the battery and BLDC motor on the ADEV 01 Monalisa Electric Car in a static state are good because the reading error is 0.60% and 0.50%. As for testing while running, namely 0.90% and 0.86%. Testing on the Internet of Things is successfully sent with a stable and fixed delay. therefore this parameter is good for monitoring electric vehicles. Researchers conducted distance testing for the Internet of Things using Thinger.io which aims to find out how far the internet connection can send sensor readings to Thinger.io. so the results obtained that a distance of 230 meters the internet connection is disconnected and cannot send data to Thinger.io.